Professional Designing Development for Change - Hawkins , Kara (Journal of Interdisciplinary Studies in Education, 2014)
Professional Designing Development for Change, as a tool for improvement which could be used during a book study amongst educators in a small group. Professional development within the workplace allows employees the ability to study material related to their profession. Studying professional development should be a priority topic in all careers. As an educator, I found this book a valuable resource for teachers, educators and administrators. This book outlines strategies and stages that promote active learning in the classroom. Educators, mainly classroom teachers can use effective techniques through development stages to improve student success.